Preventive measures for safety and helth at work with the amphibious transporter PTS-M - Kovačević, Nenad V. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Nowadays, the knowledge of using the amphibious transporter STM-M ( STM-M) is very limited. A small number of professional soldiers in the Serbian Armed Forces know how to use thisvery useful and high-quality military vehicle in a regular way. From the day onethis vehicle has remained in its basic shape without any modifications since it was made in the former Soviet Union. Today, the Serbian Armed Forces have only 12 of these vehicles in the operational use. The Serbian Armed Forces have two amphibious platoons in two pontoon batalions in the River Flotilla. As the author of this article was an officer in charge of maintaining this complex and “unusual” vehicle, the article deals with the provisions from the Regulations on preventive measures for safety and health while using work equipment (Ministry of Labour, 2012), applied to work with STM-Ms, The article makes a parallel between the provisions of the Regulations and the actual situation and specific conditions of using and maintaining STM-Ms . Introduction Some basic information about the STM-M is given here, twith Figure 1 of this vehicle and its tactical and technicalspecifications.The dangerous places onthe vehicle are presented as well. Mesuares and rules for safe work This part ofthe article presents all speciall tools on the STM-M that are used for safe work. Each piece of tool is described in detail -itslocationon the STM-M, its physical characteristics, and most common mistakes during its use. Some measures for better maintenance and improved safety at work are also proposed. Conclusion The conclusion deals with the misuse and wrong maintenance of STM-Ms and gives some proposals for their better use. A critical commentary about the conditions of safety engineering in the Serbian Armed Forces can be found here as well.